Dynamic Routing and Scheduling Optimization for Cold Chain Vehicles in Vaccine Distribution Networks - Kasaetip , Kittikorn; Wang, William Yu Chung (Science, Technology, and Social Sciences Procedia, 2023)
This paper explores to optimize dynamic routing and scheduling for cold chain vehicles in vaccine distribution networks. The paper focuses on providing sophisticated algorithms that can react to changes in real-time, realizing the importance of effective vaccination distribution for global health, especially during pandemics. These algorithms enable the timely and accurate distribution of medicinal goods that are sensitive to temperature changes by utilizing a combination of historical and real-time data along with predictive analytics. The proposed methodology includes a well-structured approach starting from data collection to algorithm development, simulation, and real-world testing. The integration of these technologies and algorithms into vaccine delivery networks holds significant potential for enhancing the effectiveness, economy, and security of logistics processes. The outcome of this research holds the potential to not just revolutionize cold chain logistics in the pharmaceutical industry, but also in a variety of industries, such as the food industry, where the integration of real-time data and predictive analytics, guarantees effective cold chain logistics while lowering operating costs and environmental effects.